Spatial analysis of fires in Vilnius city in 2010–2012 - Vasiliauskas, Darius; Beconytė, Giedrė (Geodesy and Cartography, 2015)
The paper describes the results of investigation into urban fires in the city of Vilnius, Lithuania in the three-year period of 2010–2012. Cartographic and geospatial analysis of fires is needed due to dynamism of this phenomenon, risks for inhabitants, importance to city’s socio-economic development and lack of geographic approach to research of urban fires in Lithuania. The registered fires were mapped and grouped by their type (abandoned building fires, open space fires, fires in tower blocks of flats, garbage can fires, vehicle fires and arsons), cause, location type (open space and premises) and by fatality rate. Spatial distribution of fires at different scales was analysed using cartographic method and spatial analysis with GIS. Some unexpected patterns have been revealed, analysed and compared with building materials that dominate in different areas of the city. It was found out that relative frequency of fires depends on complex parameters of socio-demographic environment whereas constructional materials have little or no impact. We expected to observe a relationship between criminal activities and fires due to similar influencing socio-demographic factors. Positive correlation, though insignificant, supported this hypothesis. The study showed that fire distribution patterns may be very specific for an individual city and difficult to explain by general assumptions. Different methods of spatial, statistical and cartographic analysis must be combined in order to make reliable generalisations.